EFISIENSI TEKNIS USAHATANI UBI JALAR DI DESA CIKARAWANG KABUPATEN BOGOR JAWA BARAT - Farah Ratih; Harmini Harmini (Forum Agribisnis, 2012)
The objectives of the research are (1) to analyze the income of sweetpotatoes farming in Cikarawang Village, (2) to analyze factors that influence the sweetpotatoes production, and (3) to analyze the technical efficiency sweetpotatoes farming. Research are carried out during March-April of 2012 in Cikarawang Village, Bogor District, West Java. The primary dataareobtained through interview with 35 sweetpotatoes farmers. To analyze the data, the stochastic frontier production function approach and farming income analysis are applied. The result shows that, first,the income of farmers with land more than 0,5 hectare are Rp 12.344.377 per hectare per season. However, farmersthat own less than 0,5 hectare only obtained Rp 1.909.161 per hectare per season. Second, the R/C quotient of sweetpotatoes production that reach >1shows that the sweetpotatoes production are profitable. Third, factors that influence the sweetpotatoes production are land size, labor, fertilizer, and pesticide. Fourth, the average technical efficiency that reach 0.564 shows thatthe sweetpotatoes farming onlyreach 56.4 percent of the maximum productivity. The research reveals that low technical efficiency of the sweetpotatoes farming are related with experience and age of the farmer. To increase the sweetpotatoes production, government should strongly promote and disseminate the production innovation and post harvest technology.